Does Greater Banking Inclusion Enhance or Undermine Banking Stability in Tunisia? Evidence from a Nonlinear Analysis - Meriem Sebai; Omar Talbi (Naše gospodarstvo/Our economy, 2026)
This paper employs a panel smooth transition regression approach to investigate the relationship between banking inclusion and banking stability in Tunisia over the period 2006–2022. Considering various dimensions of banking stability, our findings indicate an inverted U-shaped relationship between banking inclusion and stability. This indicates that banking inclusion is pivotal for strengthening banking stability up to a certain threshold. Nonetheless, once this threshold is reached, higher levels of banking inclusion lead to banking instability. This is primarily due to increased exposure to less financially experienced clients. Additionally, rapid credit expansion can strain banks’ internal risk management systems, even under strong regulatory oversight in Tunisia. This transition between regimes unfolds gradually. Our research provides essential policy implications and guidance for Tunisian financial regulators in designing strategies to balance banking inclusion and banking stability.